2014
DOI: 10.17576/3l-2014-2003-05
|View full text |Cite
|
Sign up to set email alerts
|

Creativity and Unnaturalness in the Use of Phrasal Verbs in ESL Learner Language

Abstract: Interest in ESL learner language has gained momentum since the 1990s with the generation of learner corpora, development of robust Concordance software and the establishment of the principles of the corpus --linguistic methodology. All these innovations have empowered researchers to investigate not only the frequent but also the idiosyncratic features of different language phenomena in learner language. This corpus-based content analysis stydy was an attempt to explore the phenomena of creativity and unnatural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
(13 reference statements)
1
14
0
Order By: Relevance
“…In line with those theories, learning styles are presumed to affect L2 learning (Zarifi & Mukundan 2014) and are thus defined as traits of a composite nature involving cognitive, affective and physiological facets which are relatively stable, indicating how learners perceive, interact with and react to the learning environment (Keefe, 1979). Despite the variations in definitions used, it seems that the theoretical basis for individual differences arguably arises from cognitive theories with any act of learning predicating the direction that such processes come to provide (Dornyei 2005).…”
Section: Lexical Inferencing Perceptual Styles and Language Learningmentioning
confidence: 99%
“…In line with those theories, learning styles are presumed to affect L2 learning (Zarifi & Mukundan 2014) and are thus defined as traits of a composite nature involving cognitive, affective and physiological facets which are relatively stable, indicating how learners perceive, interact with and react to the learning environment (Keefe, 1979). Despite the variations in definitions used, it seems that the theoretical basis for individual differences arguably arises from cognitive theories with any act of learning predicating the direction that such processes come to provide (Dornyei 2005).…”
Section: Lexical Inferencing Perceptual Styles and Language Learningmentioning
confidence: 99%
“…This finding is in line with the previous research, which has reported L2 learners' underuse or avoidance of PVs (Dagut & Laufer 1985, Laufer & Eliasson 1993, Sjöholm 1995. It has been argued that a majority of the problems regarding L2 acquisition of PVs are attributable to the lack of PVs in their L1 (Zarifi & Mukundan 2014). For example, Laufer & Eliasson (1993) found that Hebrew-speaking learners of English whose mother tongue does not have PVs significantly avoided PVs compared to Swedish-speaking learners of English whose mother tongue has PVs.…”
Section: Discussion Underuse Of Pvsmentioning
confidence: 99%
“…In Malaysian context, as far as the researcher is concerned, to date, there are few studies which have used a corpus based analysis to highlight the Malaysian students' inappropriate use of phrasal verbs and strategies they adopt in avoiding the use of phrasal verbs in their writings (Akbari, 2009;Rafidah Kamarudin, 2013;Zarifi & Mukundan, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For Malaysian learners, the students' lack of lexical knowledge in L2, unawareness of the idiomatic expressions of phrasal verbs (Zarifi & Mukundan, 2014) as well as influence of learners' L1 to certain extent, have been reported as the reasons for the occurrence of inappropriate uses of phrasal verbs in their English writings (Rafidah Kamarudin & Azmi Abdul Latiff, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation